Authoritarianism in Modern Germany History. Issue 1 (28th March 2018) - Meng, Michael
Abstract : Why study the history of modern German-speaking Central Europe? If pressed to answer this question fifty years ago, a Germanist would likely have said something to the effect that one studies modern German history to trace the "German" origins of Nazism, with the broader aim of understanding authoritarianism. While the problem of authoritarianism clearly remains relevant to this day, the nation-state-centered approach to understanding it has waned, especially in light of the recent shift toward transnational and global history. The following essay focuses on the issue of authoritarianism, asking whether the study of German history is still relevant to authoritarianism. It begins with a review of two conventional approaches to understanding authoritarianism in modern German history, and then thinks about it in a different way through G. W. F. Hegel in an effort to demonstrate the vibrancy of German intellectual history for exploring significant and global issues such as authoritarianism.